Evaluation and planning of the sustainable forest management in landscape level in Hojancha, Costa Rica - Serrano Dávila, Manuel (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2005